Pengaruh Tipe Propagasi Two Ray Ground dan Free Space terhadap Konsumsi Energi Protokol Destination Sequenced Distance Vector (DSDV) pada Mobile Ad Hoc Network (MANET) - Indra Lesmana Putra; Dany Primanita Kartikasari; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
MANET is a dynamic wireless network. Each node in MANET has a function as a host to connect to the wireless network and also as a router that functions to forward data packets to other nodes. In a MANET system, MANET is expected to have good performance and have a maximum level of energy efficiency. This is because each node on the MANET network requires energy to communicate with each other. In addition, the selection of propagation type can also affect of energy efficiency in MANET. In order to understand how the effect of the propagation type on energy consumption in MANET, we have conducted a study that focuses on energy consumption in MANET using two different propagation types. The two types of propagation that we used are the free space propagation type and the two ray ground propagation type. In this study, we will use the DSDV routing protocol which will regulate the routing of data transmission from the sending node to the receiving node. The DSDV protocol guarantees that there will be no looping in data transmission, so it is very suitable to be applied in this research. To achieve credible results, this study uses four test scenarios based on the number of nodes used. Each scenario will be tested 10 times using Network Simulator 2.